Therapeutic potential of targeting the IRF2/POSTN/Notch1 axis in nucleus pulposus cells for intervertebral disc degeneration - Daxue Zhu; Zhaoheng Wang; Shijie Chen; Yanhu Li; Xuewen Kang (Journal of Neuroinflammation)
Abstract Background Intervertebral disc degeneration (IDD) is a leading cause of low back pain, often linked to inflammation and pyroptosis in nucleus pulposus (NP) cells. The role of Periostin (POSTN) in IDD remains unclear. Objective This study aims to investigate the influence of POSTN on pyroptosis and NLRP3 inflammasome activation in NP cells during IDD. Methods IVD samples were collected from patients undergoing spinal surgery and classified according to the Pfirrmann grading system. Human NP cells were cultured and treated with IL-1β to induce a pyroptotic phenotype. Western blotting, Immunofluorescence (IF), and immunohistochemistry (IHC) assessed the expression levels of relevant proteins. Chromatin immunoprecipitation (ChIP) and luciferase reporter assays verified the binding of IRF2 to the POSTN and GSDMD promoters and evaluated the activation levels of target genes. The severity of IDD was evaluated using MRI and histological analysis. Results Deletion of POSTN significantly alleviated IDD by suppressing NLRP3 inflammasome activity and pyroptosis in NP cells. POSTN was found to aggravate NP cell pyroptosis by activating the NLRP3 inflammasome through the NF-κB (P65) and cGAS/STING signaling pathways. Furthermore, POSTN interacted with Notch1 to induce NLRP3 expression. IRF2 was identified as a regulator of POSTN at the transcriptional level, contributing to NLRP3 activation and NP cell pyroptosis. IRF2 also directly induced the transcriptional expression of GSDMD, mediating pyroptosis in NP cells. Chemical screening identified Glucosyringic acid (GA) as a direct inhibitor of POSTN, which delayed IDD progression. Conclusion The study elucidates the pivotal role of POSTN in mediating NP cell pyroptosis through the NLRP3 inflammasome and highlights GA as a promising therapeutic candidate for IDD. These findings provide new insights into the molecular mechanisms of IDD and potential avenues for treatment.